Impairment of amyloid precursor protein alpha-processing in cerebral microvessels of type 1 diabetic mice. Issue 6 (June 2019) - He, Tongrong; Sun, Ruohan; Santhanam, Anantha VR; d'Uscio, Livius V; Lu, Tong; Katusic, Zvonimir S
The mechanisms underlying dysfunction of cerebral microvasculature induced by type 1 diabetes (T1D) are not fully understood. We hypothesized that in cerebral microvascular endothelium, α-processing of amyloid precursor protein (APP) is impaired by T1D. In cerebral microvessels derived from streptozotocin (STZ)-induced T1D mice protein levels of APP and its α-processing enzyme, a disintegrin and metalloprotease 10 (ADAM10) were significantly decreased, along with down-regulation of adenylate cyclase 3 (AC3) and enhanced production of thromboxane A2 (TXA2 ). In vitro studies in human brain microvascular endothelial cells (BMECs) revealed that knockdown of AC3 significantly suppressed ADAM10 protein levels, and that activation of TXA2 receptor decreased APP expression. Furthermore, levels of soluble APPα (sAPPα, a product of α-processing of APP) were significantly reduced in hippocampus of T1D mice. In contrast, amyloidogenic processing of APP was not affected by T1D in both cerebral microvessels and hippocampus. Most notably, studies in endothelial specific APP knockout mice established that genetic inactivation of APP in endothelium was sufficient to significantly reduce sAPPα levels in the hippocampus. In aggregate, our findings suggest that T1D impairs non-amyloidogenic processing of APP in cerebral microvessels. This may exert detrimental effect on local concentration of neuroprotective molecule, sAPPα, in the hippocampus.